Material Requirements Planning under Phase-out Conditions - Regina Wagner; Thorsten Blecker (Operational Excellence in Logistics and Supply Chains: Optimization Methods, Data-driven Approaches and Security Insights. Proceedings of the Hamburg International Conference of Logistics (HICL), Vol. 22, 2015)
In today's production environment with shortened product lifecycles, phase-outs, i.e. product elimination from production, become regular events. Badly planned phase-outs lead to high remaining stock levels after end of production, causing immense sunk costs. Previously performed 26 interviews revealed that this is a major challenge in current production (Grussenmeyer and Blecker, 2014; Grussenmeyer, Gencay and Blecker, 2014). Therefore, the objective of this paper is to develop a material requirements planning focusing on remaining stock induced costs during phase-out to plan optimal phase-out quantity and phase-out date. The research is conceptually driven and proposes an example of the methodology.
10419/209191; https://econpapers.repec.org/RePEc:zbw:hiclpr:22
Keywords: 650; Phase-Out; Product Elimination; Production Planning and Control; Remaining Stock Costs